2022
DOI: 10.3390/ijms23179772
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates the Expression and Localization of YAP in the Uterus of Mice

Abstract: The dynamics of uterine endometrium is important for successful establishment and maintenance of embryonic implantation and development, along with extensive cell differentiation and proliferation. The tissue event is precisely and complicatedly regulated as several signaling pathways are involved including two main hormones, estrogen and progesterone signaling. We previously showed a novel signaling molecule, Serine/threonine protein kinase 3/4 (STK3/4), which is responded to hormone in the mouse uterine epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…STK3 is serine/threonine kinase 3 and plays an important role in the female reproductive system. Previous studies have shown that STK3 responded to E and P hormones in the mouse uterine epithelium ( Moon et al, 2019 , 2022 ). Moreover, STK3 was indicated as one of the key candidate genes for litter size performance in goats ( E et al, 2019 ).…”
Section: Discussionmentioning
confidence: 93%
“…STK3 is serine/threonine kinase 3 and plays an important role in the female reproductive system. Previous studies have shown that STK3 responded to E and P hormones in the mouse uterine epithelium ( Moon et al, 2019 , 2022 ). Moreover, STK3 was indicated as one of the key candidate genes for litter size performance in goats ( E et al, 2019 ).…”
Section: Discussionmentioning
confidence: 93%
“…STK3 is a key molecule in the Hippo pathway, which is highly expressed in the endometrium [ 39 ]. The activity of the STK3/ Hippo pathway is activated through estrogen and its receptor [ 40 , 41 ], and then regulates angiogenesis, cell proliferation and differentiation, and apoptosis in the endometrium, thus increasing the risk of EP. Moreover, the STK3/Hippo pathway participates in immune regulation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the liver, estrogen is also a vital regulatory hormone in the ovaries. Using estrogen in ovariectomized mice upregulates the phosphorylation of YAP in a time‐dependent manner, then decreases the YAP‐targeted genes expression in endometrial cells 57 . Moreover, ERα also plays a role in regulating Src‐induced YAP activation.…”
Section: The Regulation Of Yap/tazmentioning
confidence: 99%
“…Using estrogen in ovariectomized mice upregulates the phosphorylation of YAP in a time‐dependent manner, then decreases the YAP‐targeted genes expression in endometrial cells. 57 Moreover, ERα also plays a role in regulating Src‐induced YAP activation. In ERα overexpression MCF‐7 cell, the upregulated ERα can phosphorylate YAP at Tyr357 and then enhance the expression of its downstream gene connective tissue growth factor (CTGF) through enabling Src tyrosine kinase.…”
Section: The Regulation Of Yap/tazmentioning
confidence: 99%